TECTONIC ORIGIN OF THE 1994 SEISMICITY AT THE WESTERN PACIFIC MARGIN - Rogozhin E.A.; Zakharova A.I. (My University, 1999)
The locations of great earthquakes that occurred in 1994 at the eastern margin of the Eurasian continent were examined in relation to the geology and geophysics of the region. These data are used to derive a seismotectonic model for the contemporary evolution of the active Pacific margin. It is concluded that seismicity increased in the region in 1994-1995. The main causes of this development are discussed.